The first complete mitochondrial genome of Phellinus pomaceus var. prunastri (Pers.) Pat. 1926 (Hymenochaetales: Hymenochaetaceae) and phylogenetic analysis - Wei Gao; Shuyi Chen; Qiang Li (Mitochondrial DNA. Part B. Resources)
Phellinus pomaceus var. prunastri (Pers.) Pat. 1926 is a famous medicinal fungus that has attracted considerable interest in biotechnology because of its diverse biologically active ingredients. Here, we provide the full mitochondrial genome sequence of P. pomaceus, which spans 122,850 bp and has a GC content of 26.04%. The genome comprises 15 essential protein-coding genes, 26 distinct ORFs, 24 intronic ORFs, 25 tRNAs, and 2 rRNA genes. Bayesian inference (BI) was employed for phylogenetic analysis, revealing the evolutionary relationships among 17 Basidiomycota fungi. The results strongly supported distinct clades and indicated that P. pomaceus is closely related to Fomitiporia mediterranea.